Sirtuin1 meditated modification of Notch1 intracellular domain regulates nucleolar localization and activation of distinct signaling cascades - Saini, Neetu; Bheeshmachar, Geetha; Sarin, Apurva (Frontiers in Cell and Developmental Biology, 2022)
Notch signaling is involved in cell fate decisions in the development and maintenance of tissue homeostasis. Spatial regulation of the Notch1 intracellular domain (NIC1), has been shown to underpin signaling outcomes mediated by this receptor. We recently reported functional consequences arising from the localization of the protein Notch4, guided by a Nucleolar Localization Sequence (NoLS). Here we investigate if the putative NoLS identified in NIC1 regulates activity. Confocal imaging of live cells expressing NIC1 or forms modified by deletion or site-directed mutagenesis, established that a NoLS in the NIC1 was required for nucleolar localization, and its regulation by the deacetylase Sirtuin1. Subsequent analysis of anti-apoptotic activity revealed signaling cascades linked to nucleolar localization. For this assay, etoposide and 4-Nitroquinoline 1-oxide, an inhibitor of topoisomerase-II and a UV mimetic drug respectively, were used as prototypic triggers of genomic damage in a mammalian cell line. While NIC1 blocked apoptosis regardless of its localization to the nucleoplasm or nucleolus, localization to the nucleolus triggered a dependence on the nucleolar proteins fibrillarin and nucleolin for anti-apoptotic activity. Further, cells co-expressing NIC1 and Sirtuin1 (but not its catalytically inactive form), confirmed both spatial regulation and the switch to dependence on the nucleolar proteins. NIC1 mediated transcription is not similarly regulated. Finally, site-directed mutagenesis showed that the NoLS lysine residues are targets of Sirtuin1 activity. Thus, NIC1 localization to the nucleolus is regulated by Sirtuin1 modification of the NoLS and triggers a distinct signaling cascade involving nucleolar intermediates for anti-apopotic activity.